Implementation of Article 7 Bandar Lampung Regulation No. 3/2022: A Fiqh Siyasah Tanfidziyyah Perspective - Andre Yuda Erlangga; Muhammad Yasir Fauzi; Rudi Santoso (Jurnal El-Thawalib, 2026)
This study analyzes the implementation of Article 7 of Bandar Lampung City Regional Regulation Number 3 of 2022 on Market Administration, which obliges the local government to maintain accessibility and traffic flow around traditional markets. The research is motivated by the continued use of public roadways as trading areas at Pasar Tani, Kemiling Subdistrict, which disrupts public order and compromises collective interests. The objective of this study is to evaluate the effectiveness of Article 7 and to examine its implementation from the perspective of fiqh siyasah tanfidziyyah. Employing a qualitative method with a juridical-empirical approach, data were obtained through semi structured interviews with five traders and three officials of the Bandar Lampung City Trade Office, as well as analysis of statutory regulations and classical and contemporary fiqh siyasah literature. The findings reveal that the regulation’s implementation remains suboptimal due to inconsistent law enforcement, limited administrative capacity, and low legal compliance among traders. From a fiqh siyasah tanfidziyyah perspective, this condition indicates the insufficient role of local government as ulī al-amr in realizing justice, public welfare, and harm prevention.